Electric and magnetic properties of titanium-cobalt-oxide single crystals produced by floating zone melting with light heating - Balbashov, A.M.; Mukhin, A.A.; Ivanov, V.Yu.; Iskhakova, L.D.; Voronchikhina, M.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Single crystals of spinel Co2TiO4, CoTiO3 of ilmenite structure and pseudobrookite CoTi2O5 were grown by means of zone melting equipment URN-2-ZM. The growth processes were performed in an air atmosphere with a speed 10 mm/h and a final annealing of the crystal at temperature of 1250 °C. Co2TiO4 and CoTi2O5 crystals were obtained with a diameter of 12–15 mm and length up to 60 mm, being free of any other phase inclusions and cracks. However, in the CoTiO3 crystals some controversial features were found: x-ray Laue analysis indicated high-structure perfection while an electronic microscopy revealed small amount of second phase inclusions in contradiction to known phase diagram of this system. Electrical and magnetic properties of grown Co2TiO4 and CoTiO3 single crystals were studied. Semiconducting behavior of the Co2TiO4 was established with the energy gap of 1.3 eV. No magnetic anisotropy was found in the cubic Co2TiO4 single crystals showing a magnetic behavior similar to polycrystals. The rhombohedral CoTiO3 crystals revealed a magnetic behavior of an easy plane antiferromagnet with a significant anisotropy of the transverse magnetic susceptibilities along and perpendicular to the trigonal c axis.